Gamification as a strategy used for the development of English Oral Communication - Loza Lala, Glenda Angelica (2023)
The development of oral communication represents one of the most complex challenges to be achieved during the teaching and learning process of the English language since it involves the ability to exchange ideas, messages, opinions, and information coherently through the use of listening and speaking skills. In this regard, teachers must use innovative strategies that promote the need for communication among students. From that perspective, gamification emerges as a strategy based on elements and mechanisms that capture students' attention and provide a learning environment conducive to oral skills practice. In this context, it was proposed the study entitled “Gamification as a strategy used for the development of English oral communication at Quinto Año de Educación General Básica, class A, at Fe y Alegría School, in the city of Riobamba, Chimborazo province, during the academic period February-June 2022”. This research aimed to analyze the usage of gamification as a strategy for the development of English oral communication. On this basis, the qualitative approach and the descriptive level were adopted. Likewise, the research was of a documentary bibliographical nature since relevant information was reviewed and extracted to support the theoretical bases of the topic. Regarding data collection, the observation technique was applied; furthermore, an observation guide was used in different class sessions. The results revealed that the gamification process fosters motivation, trust, and interaction within the classroom, which facilitates the development of oral communication. Moreover, the need to implement technological tools that allow the execution of gamified activities was evidenced. Finally, it was determined that it is essential to follow an organized process before, during, and after oral communication teaching to achieve a better learning experience.